The Impact of Pet Videos on Mental Health: A Comprehensive Study - Xin, Juntong (International Journal of Social Sciences and Public Administration, 2024)
This study suggests a positive association between viewing pet video materials and those affiliated with their mental health indicators, such as mood, stress, and well-being. Through the inclusion of both experimental quantitative analysis and qualitative research, we delve into the key emotional transmission mechanisms, the relevance of empathy, and the mediating effects of viewer motivation. The discovery implies that pet videos can be utilized in psychological therapies as a tool for intervention, and it also provides clues for the development of practical media mental health promotion.